Identification and Expression Analysis of Calcium-Dependent Protein Kinases Gene Family in Potato Under Drought Stress - Dekomah, Simon Dontoro; Wang, Yihao; Qin, Tianyuan; Xu, Derong; Sun, Chao; Yao, Panfeng; Liu, Yuhui; Bi, Zhenzhen; Bai, Jiangping (Frontiers in Genetics, 2022)
Calcium-dependent protein kinases (CDPKs) are a class of serine/threonine protein kinases encoded by several gene families that play key roles in stress response and plant growth and development. In this study, the BLAST method was used to search for protein sequences of the potato CDPK gene family. The phylogeny, gene structures, cis-acting elements, and expression profiles were analyzed. Twenty-five CDPK genes in the potato genome were identified based on RNA-seq data and were clustered into four groups (I-IV) based on their structural features and phylogenetic analysis. The result showed the composition of the promoter region of the StCDPKs gene, including light-responsive elements such as Box4, hormone-responsive elements such as ABRE, and stress-responsive elements such as MBS. Transcript abundance was measured via RT-PCR between the two cultivars and their relative expression of CDPK genes was analyzed after 15 - 25 days of drought. There were varied expression patterns of StCDPK3/13/21 and 23, between the two potato cultivars under drought conditions. Correlation analysis showed that StCDPK21/22 and StCDPK3 may be the major differentially expressed genes involved in the regulation of malondialdehyde (MDA) and proline content in response to drought stress, opening a new research direction for genetic improvement of drought resistance in potato.